2019
DOI: 10.1371/journal.pone.0213277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a nutritional intervention using pictorial representations for promoting knowledge and practices of healthy eating among Brazilian adolescents

Abstract: This study aimed to evaluate the effect of a nutritional intervention involving a problem-raising approach and the use of pictorial representations on the promotion of knowledge and practices of healthy eating among adolescents. This randomized study included 461 adolescents from public schools in Brasilia, Federal District, Brazil (intervention group: 273 students from four schools; control group: 188 students from three schools). Mean age was 14.8±1.0, and 52.9% were boys. The intervention consisted of three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 32 publications
2
32
0
4
Order By: Relevance
“…It has already been demonstrated that nutritional knowledge is able to influence FCR [8]. A number of studies has found a positive correlation between nutritional knowledge and healthy dietary habits [9][10][11][12][13][14]. The knowledge transfer about the sugar content of food seems to be a promising starting point for such interventions because large proportions of calories are consumed in the form of sugar [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has already been demonstrated that nutritional knowledge is able to influence FCR [8]. A number of studies has found a positive correlation between nutritional knowledge and healthy dietary habits [9][10][11][12][13][14]. The knowledge transfer about the sugar content of food seems to be a promising starting point for such interventions because large proportions of calories are consumed in the form of sugar [15].…”
Section: Introductionmentioning
confidence: 99%
“…O reconhecimento mais contundente das categorias 1 e 4 da classificação NOVA, respectivamente, in natura e minimamente processados e ultraprocessados e o uso de termos populares, em especial, "alimento industrializado" associado a "alimento não saudável" também já foi observado tanto em estudos com adolescentes como com adultos [5,21,22].…”
Section: (A1) Pipoca Por Exemplo Feita Em Casa Eu Achava Que Era Alim...unclassified
“…As recomendações atuais, baseadas na extensão e propósito do processamento em detrimento do perfil de calorias e nutrientes, adota a regra de ouro: prefira os alimentos in natura e minimamente processados e preparações culinárias a base destes alimentos e evite os alimentos ultraprocessados [2]. No entanto, evidências apontam conhecimento insuficiente dos adolescentes sobre o sistema NOVA [4][5][6]. Adicionalmente, crianças e adolescentes com obesidade apresentam cinco vezes mais chance de continuarem com obesidade na vida adulta quando comparados a crianças e adolescentes eutróficos [7].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…In addition, when calculating the minimum sample, an estimated loss of 31.8% was added between preintervention and postintervention. 29 Thus, the minimum sample was 390 individuals: 38 in the CG, 38 in the GG and 314 in the TG.…”
Section: Interventionmentioning
confidence: 99%